Targeting Cognitive Impairment in Multiple Sclerosis—The Road toward an Imaging-based Biomarker - Van Schependom, Jeroen; Nagels, Guy (Frontiers in Neuroscience, 2017)
Multiple Sclerosis (MS) is a neurodegenerative and –inflammatory disease leading to physical and cognitive impairment, pathological fatigue and depression, and affecting patients’ quality of life and employment status. The combination of inflammation, demyelination and neurodegeneration leads to the emergence of MS lesions, reduced white and grey matter brain volumes, a reduced conduction velocity and microstructural changes in the so-called Normal Appearing White Matter (NAWM). Currently, there are very limited options to treat cognitive impairment and its origin is only poorly understood. Therefore, several studies have attempted to relate clinical scores with features calculated either using T1- and/or FLAIR weighted MR images or using neurophysiology. The aim of those studies is not only to provide an improved understanding of the processes that underlie the different symptoms, but also to develop a biomarker – sensitive to therapy induced change – that could be used to speed up therapeutic developments (e.g. cognitive training / drug discovery / …). Here, we provide an overview of studies that have established relationships between either neuro-anatomical or –neurophysiological measures and cognitive outcome scores. We discuss different avenues that may help to improve the prediction of cognitive impairment, and how well we can expect them to predict cognitive scores.